Common Immune-Related Adverse Events of Immune Checkpoint Inhibitors in the Gastrointestinal System: A Study Based on the US Food and Drug Administration Adverse Event Reporting System - Bai, Xiaoyin; Jiang, Shiyu; Zhou, Yangzhong; Zhen, Hongnan; Ji, Junyi; Li, Yi; Ruan, Gechong; Yang, Yang; Shen, Kaini; Wang, Luo; Li, Guanqiao; Yang, Hong (Frontiers in Pharmacology, 2021)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, but immune-related adverse events (irAEs) in digestive system commonly occur. In this study, we obtained data from US Food and Drug Administration adverse events reporting system between July, 2014 and April, 2020. Colitis, hepatobiliary disorders and pancreatitis were used as the irAEs investigated in our study. Reporting odds ratio (ROR) along with information component (IC) were adopted to implement a disproportionate analysis. 48,319 reports of adverse events were identified during the selected period, among them 3,140 records were associated with ICIs. Increased digestive toxicities have been observed with ICI, with ROR025 of 2.2, 6.4 and 2.4, respectively for colitis, hepatobiliary disorders and pancreatitis. Higher risk of colitis was observed with anti-CTLA-4 treatment compared with anti-PD-1 (ROR025 4.0) or anti-PD-L1 treatment (ROR025 5.2) while no difference been detected in hepatobiliary disorders and pancreatitis. Logistic analysis indicated hepatobiliary disorders occurred more commonly in female patients (OR-adjusted 1.18, p=0.007). Consistently, polytherapy was a strong risk factor for colitis (2.78, p<0.001), hepatobiliary disorders (2.67, p<0.001) and pancreatitis (2.13, p<0.001) based on multivariate logistic analysis. This pharmacovigilance analysis demonstrated an increased risk of all the three digestive irAEs associated with ICIs therapies. The real-world comparative analysis offered supportive insights on selecting digestive irAEs for patients treated with ICIs therapies.